PU.1 and Haematopoietic Cell Fate: Dosage Matters - Ka Sin Mak; Alister P. W. Funnell; Richard C. M. Pearson; Merlin Crossley (International Journal of Cell Biology)
The ETS family transcription factor PU.1 is a key regulator of haematopoietic differentiation. Its expression is dynamically controlled throughout haematopoiesis in order to direct appropriate lineage specification. Elucidating the biological role of PU.1 has proved challenging. This paper will discuss how a range of experiments in cell lines and mutant and transgenic mouse models have enhanced our knowledge of the mechanisms by which PU.1 drives lineage-specific differentiation during haematopoiesis.